Bridging the Training-to-Classroom Gap: A Kirkpatrick Evaluation of Teacher Professional Development in Rural Indonesia - Zikri Rakhman; Muh Yusup (Qualitative and Quantitative Research Center, 2026)
While global investments in teacher professional development (TPD) have surged, the